A novel small-molecule inhibitor of endosomal tlrs reduces inflammation and alleviates autoimmune disease symptoms in murine models - Patra, Mahesh Chandra; Achek, Asma; Kim, Gi Young; Panneerselvam, Suresh; Shin, Hyeon Jun; Baek, Wook Yong; Lee, Wang Hee; Sung, June; Jeong, Uisuk; Cho, Eun Young; Kim, Wook; Kim, Eunha; et al. (Cells, 2020)
Toll-like receptors (TLRs) play a fundamental role in the inflammatory response against invading pathogens. However, the dysregulation of TLR-signaling pathways is implicated in several autoimmune/inflammatory diseases. Here, we show that a novel small molecule TLR-inhibitor (TAC5) and its derivatives TAC5-a, TAC5-c, TAC5-d, and TAC5-e predominantly antagonized poly(I:C) (TLR3)-, imiquimod (TLR7)-, TL8-506 (TLR8)-, and CpG-oligodeoxynucleotide (TLR9)-induced signaling pathways. TAC5 and TAC5-a significantly hindered the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), reduced the phosphorylation of mitogen-activated protein kinases, and inhibited the secretion of tumor necrosis factor-α (TNF-α) and interleukin-6. Besides, TAC5-a prevented the progression of psoriasis and systemic lupus erythematosus (SLE) in mice. Interestingly, TAC5 and TAC5-a did not affect Pam3CSK4 (TLR1/2)-, FSL-1 (TLR2/6)-, or lipopolysaccharide (TLR4)-induced TNF-α secretion, indicating their specificity towards endosomal TLRs (TLR3/7/8/9). Collectively, our data suggest that the TAC5 series of compounds are potential candidates for treating autoimmune diseases such as psoriasis or SLE.
Keywords: Animals; Anti-Inflammatory Agents; Binding Sites; Endosomes; Female; Immunologic Factors; Interleukin-6; Lupus Erythematosus, Systemic; Mice; Mice, Inbred C57BL; Molecular Docking Simulation; NF-kappa B; Protein Binding; Psoriasis; Quantitative Structure-Activity Relationship; RAW 264.7 Cells; Small Molecule Libraries; Toll-Like Receptors; Tumor Necrosis Factor-alpha; Antagonist; Autoimmune diseases; Endosomal TLR; QSAR; TAC5; Toll-like receptor